Red Palm Oil Attenuates Lead Acetate Induced Testicular Damage in Adult Male Sprague-Dawley Rats. (21st September 2015) - Jegede, A. I.; Offor, U.; Azu, O. O.; Akinloye, O.
Abstract : To study the protective effect of Red Palm Oil (RPO) on testicular damage induced by administration of lead acetate on male Sprague-Dawley rats, 28 rats divided into four groups of 7 animals each were used. They were administered orally with RPO (1 mL and 2 mL) and lead acetate (i.p.) 6 mg/kg body weight/day, respectively. Treatment was conducted for 8 weeks, and 24 hrs after the last treatment the rats were sacrificed using cervical dislocation. Sperms collected from epididymis were used for seminal fluid analyses; while the testes sample was used for ROS and oxidative enzyme activities assessment. Statistical analysis was carried out using GraphPad Prism 5.02 statistical analysis package. Administration of lead acetate increased generation of reactive oxygen species (ROS) significantly (p < 0.05 ) as evidenced by the elevated value of H2 O2 and LPO and decreased GSH level. Also there was reduced epididymal sperm count, poor grade of sperm motility, and lower percentage of normal sperm morphology significantly. Coadministration with RPO, however, has a protective effect against lead toxicity by decreasing H2 O2 production, increased GSH level, and increased sperm qualities especially. This shows that RPO has a potential to attenuate the toxic effect of lead on testicular cells preventing possible resultant male infertility.